The articular cartilage surface is impaired by a loss of thick collagen fibers and formation of type I collagen in early osteoarthritis. (1st July 2022) - Tschaikowsky, Mathaeus; Brander, Sofia; Barth, Vanessa; Thomann, Ralf; Rolauffs, Bernd; Balzer, Bizan N.; Hugel, Thorsten
Abstract: Osteoarthritis (OA) is a joint disease affecting millions of patients worldwide. During OA onset and progression, the articular cartilage is destroyed, but the underlying complex mechanisms remain unclear. Here, we uncover changes in the thickness of collagen fibers and their composition at the onset of OA. For articular cartilage explants from knee joints of OA patients, we find that type I collagen-rich fibrocartilage-like tissue was formed in macroscopically intact cartilage, distant from OA lesions. Importantly, the number of thick fibers (>100 nm) has decreased early in the disease, followed by complete absence of thick fibers in advanced OA. We have obtained these results by a combination of high-resolution atomic force microscopy imaging under near-native conditions, immunofluorescence, scanning electron microscopy and a fluorescence-based classification of the superficial chondrocyte spatial organization. Taken together, our data suggests that the loss of tissue functionality in early OA cartilage is caused by a reduction of thick type II collagen fibers, likely due to the formation of type I collagen-rich fibrocartilage, followed by the development of focal defects in later OA stages. We anticipate that such an integrative characterization will be very beneficial for an in-depth understanding of other native biological tissues and the development of sustainable biomaterials. Statement of significance: In early osteoarthritis (OA) the cartilage appears macroscopically intact. However, this study demonstrates that the collagen network already changes in early OA by collagen fiber thinning and the formation of fibrocartilage-like tissue. Both nanoscopic deficiencies already occur in macroscopically intact regions of the human knee joint and are likely connected to processes that result in a weakened extracellular matrix. This study enhances the understanding of earliest progressive cartilage degeneration in the absence of external damage. The results suggest a determination of the mean collagen fiber thickness as a new target for the detection of early OA and a regulation of type I collagen synthesis as a new path for OA treatment. Graphical abstract: Image, graphical abstract